Molecular diagnostic investigation of brucellosis in a caprine organic farm - IKONOMOPOULOS (I.A. ΟΙΚΟΝΟΜΟΠΟΥΛΟΣ) J. A.; GAZOULI (M. ΓΑΖΟΥΛΗ) M.; XYLOURI (Ε. ΞΥΛΟΥΡΗ) E.; GEORGAKILAS (E.K. ΓΕΩΡΓΑΚΙΛΑΣ) E. K.; KARAGIANNI (Π. ΚΑΡΑΓΙΑΝΝΗ) P.; MENEGATOS (Ι. ΜΕΝΑΓΑΤΟΣ) I. (Journal of the Hellenic Veterinary Medical Society, 2017)
Brucellosis of sheep and goats is widely spread in the Mediterranean basin. The disease is of considerable significance with connection to Public Health protection since it can be transmitted to humans causing serious disease. In April 2005 we investigated whether brucellosis was present among the male animals of a caprine organic herd in Nomos Hleias, Greece. The herd consisted of 250 female and 13 male animals and had a record of sporadic abortions usually taking place at the final third of gestation. During sample collection all the animals were found clinically healthy, although it was not possible to determine from the records of the farm if there was any previous incidence of orchitis or epididymitis in the animals under study. The laboratory diagnostic investigation consisted of a polymerase chain reaction (PCR) assay applied for the detection of DNA belonging to Brucella melitensis in blood samples. Two of the 13 samples that were tested reacted positive by PCR allowing the amplification of the 844 base pair DNA fragment specific for Brucella melitensis. In this study, PCR allowed detection of two animals that although they were clinically healthy, they carried enough Brucella in their blood to allow microbial identification with only a single blood collection. This finding seems to agree with the concept that goats consist the reservoir of brucellosis in Greece developing milder disease than sheep and sustaining the infection for longer periods of time. One of the positive samples that were recorded was identified by sequencing as Brucella suis, something that is reported for the first time with connection to goats. This finding and the sensitivity of man to B. suis renders human exposure to this pathogen through goats, an epidemiology factor worth of detailed investigation. This necessity is associated with the fact that as opposed to porcine meat, sheep and goat dairy products in Greece are sometimes consumed without the necessary heat treatment.